Interface Mechanical Behavior of Unstabilized Earth Block–Palm Fiber Composites: Experimental and Analytical Pull-Out Analysis - Candelot-Hours, Enzo; Boyer, Benjamin; Diomande, Abdoulatif; Fouchal, Fazia; Abbes, Fazilay; Abbes, Boussad (Journal of Composites and Biodegradable Polymers, 2026)
The development of sustainable construction materials has renewed interest in bio-based fiber-reinforced earthen composites; however, the mechanical performance of these materials is governed by the fiber–matrix interface, which remains poorly quantified. This study presents an integrated experimental–numerical investigation of the interface behavior between date palm fibers (DPFs) and unstabilized earth blocks. The experimental program combined tensile testing of DPFs using Digital Image Correlation, compression tests on raw earth, and single-fiber pull-out tests to characterize interfacial behavior from adhesion to frictional sliding. The results show an average Young’s modulus of 7.42 GPa for DPFs, 38.09 MPa for raw earth, and an interface stiffness of 487.17 MPa/m. Pull-out tests enabled identification of key interfacial parameters governing load transfer mechanisms. A numerical model adapted from Gontero’s formulation was developed using an equivalent diameter approach to represent the flat geometry of palm fibers while preserving the contact surface. The model successfully reproduces the experimental pull-out response and captures the transition from adhesion to friction-dominated behavior. This work provides an experimentally calibrated micromechanical framework for predicting the behavior of palm fiber–reinforced earthen composites and contributes to the performance-based design of sustainable bio-reinforced construction materials.
Keywords: Bio-based materials; Earthen composites; Mechanical modeling; Palm fibers; Pull-out test; Sustainable construction material